Establishment of a value assessment framework for orphan drugs in China: an application of the discrete choice experiment in multicriteria decision analysis - Zhao, Zhihao; Tang, Xian; Hu, Ming (Frontiers in Pharmacology, 2025)
ObjectivesThe medical security of orphan drugs faces difficulty in basic medical insurance access in China. Conventional cost-effectiveness analysis in the access process lacks broader value concerns and a value assessment framework is needed. This study aims to construct a multicriteria decision analysis value assessment framework for orphan drugs using the discrete choice experiment method from the perspective of basic medical insurance access in China.MethodsThe attributes and levels of the framework were identified through literature and reports review. An unlabeled discrete choice experiment was employed to determine the relevance and relative importance weight of such attributes for decision-making. Questionnaire was designed based on D-efficient design. Survey was conducted anonymously using an online survey platform. A mixed logit model estimated the DCE responses.ResultsSeven attributes (disease severity, unmet needs, drug efficacy, improvement in health-related quality of life, drug safety, quality of drug evidence, and annual treatment cost per patient reimbursed by basic medical insurance) were selected with three levels for each. It formed three parallel questionnaires, each containing 11 paired choice sets. A total of 84 respondents completed the study, and 69 questionnaires were valid. The results showed that six of the seven attributes were significant, except for ‘Unmet needs’. Among all attributes and levels, the respondents exhibited the highest WTP (567,900 RMB/year) for ‘significant improvement in usual activities’. Based on discrete choice model, the most important attributes measured by their relative importance weights are: improvement in health-related quality of life (23.44%), disease severity (18.65%) and annual treatment cost per patient reimbursed by basic medical insurance (17.34%). Different types of respondents and weighting methods may lead to slight variations in the results.ConclusionOur study provides a new research perspective and methodological support for the value assessment of orphan drugs. When establishing a value assessment framework for orphan drugs in China, overall, the medical insurance access prioritized disease severity, and improvement in health-related quality of life. The application of discrete choice experiment proves to be a powerful tool for weighting criteria in healthcare multicriteria decision analysis framework and should be further explored for the value assessment of orphan drugs. Our findings offer a structured, evidence-based framework to support access and reimbursement decisions for orphan drugs.